SUFISME MAHASISWA: WAWASAN KEBANGSAAN INKLUSIF BERBASIS TASAWUF - Alaika M. Bagus Kurnia PS Alaika; Muhamad Basyrul Muvid; Risma Savhira D. L. (Fakultas Agama Islam Universitas Wiralodra, 2021)
Sufi is an activity that gives an ethical and spiritual touch to the community. In the midst of its development, on the other hand there is homework for the Sufi group to take part. Because of the moral decadence among students, their concern for the integrity of the ideology of the nation and the state is no longer in the realm of indifference, but rather contra and wishes to change it. So that the purpose of this article is to respond to the open insight of student nationality with the Sufism approach. The method used in this research is descriptive-qualitative. The result is a national insight for students as a motor in preserving the ideology of national and state sovereignty. Sufi groups' concern among students for government politics in a participatory and accommodating manner is a field of pious charity for him as an actualization to maintain a comfortable arena of spiritual activity. Apart from being an effort at tazkiyatun nafsi.